Role of Organosulphur acid of the Conductance of PANI-Computational and Physico-Chemical Studies (International Journal of Food and Nutritional Sciences, 2021)
Sulphur acids have much different behaviour than a carboxylic acid. Sulphur has a different role due to its bulkiness and electron donating ability. This work has the composites of PANI with sulphur acids. The behaviour of PANI in the presence of sulphur acid is studied by DFT, TDFT, spectra and conductance for four different compositions. Conductance of PANI is reduced by composting by sulphur acids. The order of conductance of composites is PANI-BCG > PANI-PRR > PANI-SA. The role of altering the conductance is electronic over structural. The conductance is by hoping of H+ in the field created by the counterion chloride and polymer.